Comparison of HRCT chest findings among vaccinated and non-vaccinated COVID-19 patients - Kumari, Neha; Ahmad, M. Shamim; Gupta, Animesh; Prakash, Gaurav (International Journal of Research in Medical Sciences, 2022)
Background: Coronavirus disease 19 was first reported in Wuhan, China and it was declared a pandemic by WHO in March 12, 2020. Vaccination has provided a very effective way to prevent the spread and reduce the severity of this disease. The two vaccines currently approved by the Government of India are Covaxin and Covishield. HRCT is the most valuable tool available to assess the pulmonary involvement in this disease. The aim of the study was to assess the effect of vaccination on the severity of pulmonary involvement in COVID-19. Methods: A cross-sectional study was conducted in a department of radio diagnosis of tertiary health care hospital of Bihar for period of 4 months from April 2021 to July 2021. Results: The study involved a total of 100 patients (74 were males and 26 females), where 50 were (50%) were unvaccinated and 50 (28.6%) were vaccinated with one or both doses Covishield vaccine. The frequency of disease was least in 14 (7.9%) among fully vaccinated subjects. The CT severity score is less in those who took both doses of the vaccine. The mean CT score of all the patients included in the study was 12.64±11.1. However, the patients who received complete vaccination had significantly low mean CT scores (14.18±7.223) in comparison to the non-vaccinated patients (11.1±6.016). Fully vaccinated patients had almost low CT severity score indicating mild form of disease. Conclusions: HRCT is the most sensitive modality to detect severity of COVID-19 pneumonia. Severe lung involvement is more common in the unvaccinated population (32%) as compared with the vaccinated group, in which only 25% members had severe lung involvement.